Urgensi Dialog Lintas Agama dan Budaya dalam Masyarakat Multikultural - Yasinta Rohmawati; Tasya Tasya (Indo Publishing, 2026)
A multicultural society is characterized by diversity in religion, culture, ethnicity, language, and traditions. While such diversity enriches social life, it also has the potential to generate conflict if not managed effectively. This study aims to analyze the urgency, objectives, forms, and implementation of interfaith and intercultural dialogue in fostering harmony within multicultural societies. The research employs a qualitative method using a library research approach by analyzing various relevant literature sources. The findings indicate that interfaith and intercultural dialogue play a significant role in reducing prejudice, preventing social conflict, strengthening social cohesion, and fostering mutual respect amid diversity. Such dialogue aims to promote mutual understanding, enhance social cooperation, and develop tolerance among different groups. The forms of dialogue include the dialogue of life, dialogue of action, theological dialogue, dialogue of religious experience, as well as cultural and artistic dialogue. From an Islamic perspective, these forms of dialogue are consistent with the values of tolerance, peace, and respect for humanity. Therefore, interfaith and intercultural dialogue serve not only as a means of communication but also as a strategic instrument for building a harmonious, inclusive, and peaceful society.